Spectrophotometric and spectrofluorimetric determination of the ternary complexes of cadmium(l1) and zinc(ll) with 2,2’-Bipyridine and Rose Bengal Extra - Ishak, Che Fauziah; Pflaum, Ronald T. (Royal Society of Chemistry, 1988)
A sensitive and selective ternary complex system has been developed for the determination of cadmium(II) and zinc(II). This system consists of the metal ion. an organic base, 2. 2,2‘-bipyridine,and the fluorescein dye Rose Bengal Extra (RBE). The ternary complexes of both cadmium(l1) and zinc(ll) exhibit a sensitivity or molar absorptivity of 1.03 x lo5 and 9.97 x lo4 I mol-1 cm-1, respectively. Preliminary studies showed an enhancement of the secondary fluorescence spectra of the bipyridine - RBE complex system for cadmium(l1) and zinc(l1). This enhancement is the basis of the fluorimetric determination of cadmium(l1) and zinc(l1). This metal ion - bipyridine - RBE system has a linear fluorescence calibration range from 1.0 X 10-6 to 14.0 X 10-6 M (0.06-0.91 p.p.m. Zn” and 0.11-1.54 p.p.m. Cd11)